2003
DOI: 10.1177/0885328203017003480
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Physical Properties and Preliminary Investigation of Hemocompatibility of Polyurethanes from Aliphatic Resources with Castor Oil Participation

Abstract: The synthesis of polyurethanes (PURs) from oligoetherdiol, two low molecular diols, castor oil and 4,4'-Methylenebis(cyclohexylisocyanate) is described. These polymers are characterized by measurements of the mechanical bulk and surface properties, preliminary investigation of compatibility with human blood and calcification in static conditions. The critical surface energy of synthesized PURs is similar to the critical surface energy of natural surfaces. Material-induced hemolysis and the changes of platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…Thus, we expected that this monomer, containing long chains of oleic acid, would produce polyurethanes with greater affinity to albumins and antithrombogenic properties. Our investigation of such modified PEUs showed that the material induced low hemolysis and low changes in the level of the morphotic elements in blood 12. Seven weeks of in vitro static calcification testing did not result in calcification of the PEU containing castor oil 12…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Thus, we expected that this monomer, containing long chains of oleic acid, would produce polyurethanes with greater affinity to albumins and antithrombogenic properties. Our investigation of such modified PEUs showed that the material induced low hemolysis and low changes in the level of the morphotic elements in blood 12. Seven weeks of in vitro static calcification testing did not result in calcification of the PEU containing castor oil 12…”
Section: Introductionmentioning
confidence: 72%
“…The PEU polymer obtained in our previous work12 from polytetramethylene oxide glycol ( M n = 2000) and characterized by a similar hard segment concentration from HMDI, 1,4‐BD and 1,5‐PD, and a similar content of castor oil as PCU‐I, showed a lower σ 100% (6.3–7.2 MPa) and σ b (24.7–26.3 MPa). It also had greater ε b (545%) than PCU‐I.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another approach may be seen in nanostructured surfaces to avoid any blood cell or plasma protein adhesion [12,13]. New biomaterials, biohydrid structures, combinations of synthetic and biological polymers such as polysialic acid [Assmann U, Schuster R, Szentivaniy A, Glasmacher B: Electrospinning of polysialic acid and its blends for tissue engineering scaffolds, 2007] will also be demonstrated [8][9][10].…”
Section: Aspects Of Cardiovascular Biomaterialsmentioning
confidence: 99%
“…Unsaturated polyurethanes (uPUR), containing double bonds from polyesters soft segments [1][2][3], chain extenders [4,5] or pendant groups [6][7][8][9][10][11][12], belong to a new class of elastomers. Their importance in macromolecular chemistry follows from their possible applicability in syntheses of cross-linked polymers.…”
Section: Introductionmentioning
confidence: 99%